2017
DOI: 10.19080/jfsci.2017.03.555622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium Chloride on the Development of Chrysomya Megacephala (Diptera:Calliphoridae) and its Importance to Postmortem Interval Estimate

Abstract: Cadmium chloride is one of the highly toxic compounds among the heavy metals. It exerts a negative impact on the living organisms and accumulates in food chain and could lead to some serious problems, such as high rate of mortality, lower longevity, decreased fecundity and lower hatching ability of many insects and other arthropods. The present work dealt with the evaluation of cadmium chloride because there is lack of published entomotoxicological reports for cadmium chloride have evaluated their effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Researchers used a variety of food sources spiked with heavy metals to rear immatures; all food sources are shown in Figure 1. The most common were rats (Heer & Singh, 2019;Kaur, 2016;Singh & Bhupinderjit, 2017) injected with different concentrations of heavy metals, and artificial diets (Bessa et al, 2021;Moe et al, 2001;Simkiss et al, 1993). Additionally, ground beef (Al-Misned, 2001, 2003, chicken liver (Kökdener et al, 2022;Kökdener & Yılmaz, 2021), and pork liver (Malejko et al, 2020;Shulman et al, 2017) were used.…”
Section: Trophic Substratesmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers used a variety of food sources spiked with heavy metals to rear immatures; all food sources are shown in Figure 1. The most common were rats (Heer & Singh, 2019;Kaur, 2016;Singh & Bhupinderjit, 2017) injected with different concentrations of heavy metals, and artificial diets (Bessa et al, 2021;Moe et al, 2001;Simkiss et al, 1993). Additionally, ground beef (Al-Misned, 2001, 2003, chicken liver (Kökdener et al, 2022;Kökdener & Yılmaz, 2021), and pork liver (Malejko et al, 2020;Shulman et al, 2017) were used.…”
Section: Trophic Substratesmentioning
confidence: 99%
“…There is a consensus among the different articles that the mortality rate of both larvae and pupae of all species increased as the concentration of these heavy metals increased. Generally, larval mortality was higher than pupal mortality (Al-Misned, 2001;Heer & Singh, 2019;Singh & Bhupinderjit, 2017). Kaur (2016) found that for higher concentrations of cadmium chloride, mercuric chloride, lead acetate, and arsenic trioxide both larval and pupal mortality of C. megacephala increased; however, for the lower concentration of arsenic trioxide, there was a lower larval mortality.…”
Section: Mortality Rate and Longevitymentioning
confidence: 99%
See 3 more Smart Citations